Evaluation of the environmental sustainability in the olive growing systems in Tunisia. (1st February 2021) - Ben Abdallah, Saker; Elfkih, Saida; Suárez-Rey, Elisa M.; Parra-López, Carlos; Romero-Gámez, Mercedes
Abstract: Olive cultivation for oil production in Tunisia covers from traditional to innovate cropping systems. The aim of the study was to assess the environmental footprint of the most representative olive growing systems of the actual production of olive fruit in Tunisia, from the planting phase to the full production phase, during a reference period of the life cycle of the olive growth of 50 years. Six traditional systems, two intensive systems and one super-intensive system were compared and the differences of type of production (conventional or organic), irrigation management and fertilization management were selected. The impacts associated to olive production were calculated and evaluated by the Life Cycle Assessment methodology and the results of this study were referred to two functional units: 1 ton of olives and 1 ha of cultivated olive growing area. Field agricultural practices of olive systems were soil management, fertilizers, pesticides, pruning and harvesting. The impact categories selected for the environmental analysis were climate change, acidification, freshwater eutrophication and freshwater ecotoxicity. The most innovative olive production systems (intensive and super-intensive) resulted in less environmental impacts for all categories with respect to the rest of systems from the productive perspective but produced higher impacts per hectare of cultivated area. Fertilizers and soil management were the field agricultural practices that presented the highest contributions in most of the categories evaluated. The implementation of an integrated crop management, as well as good practice guides and training programs for farmers, should be considered a priority. Graphical abstract: Image 1 Highlights: This is the first LCA study for the olive growing systems in Tunisia. Optimizing the productivity of traditional olive systems should be a priority. The organic systems showed the lowest environmental impacts in all categories. Fertilizers was the field agricultural practice with the highest contributions. ICIF2 and SICIF showed the lowest environmental impact and highest productivity.